2007
DOI: 10.1128/jcm.01012-07
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Acute from Chronic and Resolved Hepatitis C Virus (HCV) Infections by Measurement of Anti-HCV Immunoglobulin G Avidity Index

Abstract: An assay to measure avidity index (AI) was developed to diagnose incident hepatitis C virus (HCV) infections. The assay demonstrated an AI value statistically significantly lower in primary HCV infections than in chronic infections. When the assay was applied to past resolved infections, the difference in AI values was not as significant as the difference between incident and chronic infections. Lower AI values obtained in past resolved infections may be directly related to lower levels of immunoglobulin G ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 17 publications
3
37
0
Order By: Relevance
“…16,19,23 Previous studies have found that patients with resolved HCV infection can have a lower avidity index compared to chronic patients whose antibodies are continually exposed to the HCV virus. [16][17][18][19] A testing algorithm has been developed for HCV avidity using either plasma or DBS. In our laboratory we found that two dilution factors were required to help differentiate between chronic and resolved infections when the sample had an AI < 30 and was PCR negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,19,23 Previous studies have found that patients with resolved HCV infection can have a lower avidity index compared to chronic patients whose antibodies are continually exposed to the HCV virus. [16][17][18][19] A testing algorithm has been developed for HCV avidity using either plasma or DBS. In our laboratory we found that two dilution factors were required to help differentiate between chronic and resolved infections when the sample had an AI < 30 and was PCR negative.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have addressed HCV avidity testing but all have been described using plasma/serum samples. [15][16][17][18][19] All the HCV avidity methods reported are modifications of commercial or in house ELISA kits using either guanidine or urea as the DA. The method described in this paper uses a modified commercial assay with an overnight incubation stage for HCV avidity testing.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic hepatitis C patients (the "chronic" group) consisted of anti-HCVIgG-positive plasma samples from 141 blood donors: 64 samples were from BBI, and 77 were from the American Red Cross (9). All samples were confirmed to contain anti-HCV IgG by the Ortho recombinant immunoblot assay (RIBA) and HCV RNA by reverse transcriptase PCR (9).…”
Section: Methodsmentioning
confidence: 99%
“…Further, distinguishing acute from chronic infection on the basis of clinical history, epidemiological risk factors, and symptoms can be difficult because for most patients acute infection is asymptomatic (12,3). Several approaches, which include detection of anti-HCV IgM (4,2), measurement of the anti-HCV IgG avidity index (9), and observation of serial changes in viral load (10), have been proposed as indicators of acute HCV infection. The usefulness of anti-HCV IgM as a marker of acute infection remains controversial (4,2).…”
mentioning
confidence: 99%
“…However, the limited evaluation of such assays in small populations has hampered their development for use in clinical practice. More recently, the development of an "inhouse" anti-HCV IgG avidity assay, using a combination of target antigens, has been validated with seroconversion panels and samples from chronically infected individuals (12).…”
mentioning
confidence: 99%